Differential control of Yersinia pestis biofilm formation in vitro and in the flea vector by two c-di-GMP diguanylate cyclases. - Yi-Cheng Sun; Alexandra Koumoutsi; Clayton Jarrett; Kevin Lawrence; Frank C Gherardini; Creg Darby; B Joseph Hinnebusch (PLoS ONE, 2011)
Yersinia pestis forms a biofilm in the foregut of its flea vector that promotes transmission by flea bite. As in many bacteria, biofilm formation in Y. pestis is controlled by intracellular levels of the bacterial second messenger c-di-GMP. Two Y. pestis diguanylate cyclase (DGC) enzymes, encoded by hmsT and y3730, and one phosphodiesterase (PDE), encoded by hmsP, have been shown to control biofilm production in vitro via their opposing c-di-GMP synthesis and degradation activities, respectively. In this study, we provide further evidence that hmsT, hmsP, and y3730 are the only three genes involved in c-di-GMP metabolism in Y. pestis and evaluated the two DGCs for their comparative roles in biofilm formation in vitro and in the flea vector. As with HmsT, the DGC activity of Y3730 depended on a catalytic GGDEF domain, but the relative contribution of the two enzymes to the biofilm phenotype was influenced strongly by the environmental niche. Deletion of y3730 had a very minor effect on in vitro biofilm formation, but resulted in greatly reduced biofilm formation in the flea. In contrast, the predominant effect of hmsT was on in vitro biofilm formation. DGC activity was also required for the Hms-independent autoaggregation phenotype of Y. pestis, but was not required for virulence in a mouse model of bubonic plague. Our results confirm that only one PDE (HmsP) and two DGCs (HmsT and Y3730) control c-di-GMP levels in Y. pestis, indicate that hmsT and y3730 are regulated post-transcriptionally to differentially control biofilm formation in vitro and in the flea vector, and identify a second c-di-GMP-regulated phenotype in Y. pestis.